The Influence of AI-Driven Personalization in Social Media Marketing on Consumer Purchase Decisions and Behavior - Wang, Lu; Jing , Zhang; Li , Huixiang; Li, Changlu; Su , Yuhao (International Journal of Accounting and Economics Studies, 2025)
As the digital age took over, artificial intelligence (AI) has turned out to be a powerful tool in revolutionizing marketing practices, especially in social media. AI personalization enables social media and brands to deliver content and ads that are customized and tailored to users’ information, interests, and activity. In this research, the role of AI-powered personalization in social media marketing towards influencing consumer buying behavior and activity is researched. Grounded in behavioral theories and contemporary empirical studies, the research analyzes the effectiveness of personalized marketing tactics, such as recommendation algorithms, dynamic pricing, and predictive analytics, to affect customer interaction and conversion. Based on the incorporation of existing literature and case study analysis, results indicate that AI personalization exerts a significant influence on purchase intention, customer satisfaction, brand loyalty, and impulse buying tendency. However, moral considerations such as privacy concerns and data transparency remain critical in influencing consumer trust and long-term loyalty. The study concludes with offering strategic guidelines for marketers to effectively and ethically use AI personalization.